Comprehensive School and Vocational Training in Spain. A Longitudinal Approach from the Transition from Lower to Upper Secondary Education - Rafael Merino; Ona Valls; Albert Sánchez-Gelabert (MDPI AG, 2021)
Fitting vocational training into the Spanish education system has been challenging and problematic because two objectives are trying to be fulfilled; the first to supply skills for the productive system and the second to be an alternative option for the young people who do not follow the academic track. Moreover, the political vicissitudes of recent decades have added to the difficulties involved in balancing these requirements. In Spain, both the economic agents and the education system itself with its academic inertia have relegated vocational training to a subordinate position, able to attract mainly young people with lower academic achievement and largely rejected by families with a higher educational level. The assumption was that the introduction of a comprehensive secondary education in the 1990s would provide parity between the academic and the vocational tracks. However, the comprehensive nature of this system was not fully applied, with students in many schools separated by ability levels, and in fact having little impact on the social bias of the students choosing vocational training. The empirical contribution of this study is based on a survey carried out among 2056 students from Barcelona in their last year of compulsory secondary education in 2013-14 and who continued in full-time education, be it baccalaureate or vocational training. The main result shows that comprehensive education improves school success and decreases the vocational orientation of students from low social backgrounds.